Translating findings from basic fear research to clinical psychiatry in Puerto Rico - Quirk, Gregory J.; Martínez, Karen G.; Nazario, Lelis L. (Puerto Rico Health Sciences Journal, 2007)
Recent advances in the neuroscience of classical fear conditioning from both rodent and human studies are beginning to be translated to the psychiatry clinic. In particular, our understanding of fear extinction as a form of “safety learning” holds promise for the treatment of anxiety disorders in which extinction learning is thought to be compromised. The Department of Psychiatry at the UPR, School of Medicine promotes the development of innovative strategies for treating mental health problems. Given the burden resulting from anxiety disorders in Puerto Rico, and the lack of evidence-based treatment practices, there is a pressing need for a future center specializing in the treatment of anxiety related disorders. This center would also serve research and training functions, with the ultimate goal of translating extinction research into clinical practice. This review presents the current developments in extinction research and its relationship to anxiety disorders and treatment. We also analyze the available literature on the epidemiology of anxiety disorders and the existing evidence-based treatments for these conditions.